2010
DOI: 10.1002/cncr.25362
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of paclitaxel versus pegylated liposomal doxorubicin for advanced human immunodeficiency virus‐associated Kaposi sarcoma

Abstract: Background Paclitaxel (PTX) and pegylated liposomal doxorubicin (PLD) are active cytotoxic agents for the treatment of human immunodeficiency (HIV) associated Kaposi’s sarcoma (KS). We performed a randomized trial comparing the efficacy and toxicity of PTX and PLD, and determine the effects of therapy on symptom palliation and quality of life. Methods Patients with advanced HIV-associated KS were randomly assigned to receive PTX (100 mg/m2) IV every 2 weeks, or PLD 20 mg/m2 IV every 3 weeks. The KS Functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
108
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(113 citation statements)
references
References 33 publications
3
108
0
2
Order By: Relevance
“…They authors concluded that either paclitaxel or PLD leads to improvement in symptoms of AIDS-KS including pain and difficulty swelling. Also, in accordance to their previous published work [21], the two studied drugs are active to treat AIDS-KS even in an HAART era [31]. .…”
Section: Paclitaxelsupporting
confidence: 84%
See 1 more Smart Citation
“…They authors concluded that either paclitaxel or PLD leads to improvement in symptoms of AIDS-KS including pain and difficulty swelling. Also, in accordance to their previous published work [21], the two studied drugs are active to treat AIDS-KS even in an HAART era [31]. .…”
Section: Paclitaxelsupporting
confidence: 84%
“…Von Roenn et al [21], conducted a phase III clinical trial comparing paclitaxel and liposomal doxorubicin for the treatment of advanced AIDS-KS where they found no statistical difference in efficacy, however; the study was terminated early due to slow accrual and difficulties in recruitment ( Table 2). Later in 2010, the same group published more results of the trial including data on quality of life [31]. They authors concluded that either paclitaxel or PLD leads to improvement in symptoms of AIDS-KS including pain and difficulty swelling.…”
Section: Paclitaxelmentioning
confidence: 97%
“…Anthracyclines are well tolerated despite the risk of cardiac toxicity; response rates are almost 50%, with a median of 5 months response [57]. Chemotherapy with paclitaxel shows almost the same efficacy but can interact with protease inhibitors [58,59]. Protease inhibitors, such as ritonavir, are among the most potent antiviral drugs and are often a component of cART [60].…”
Section: Differential Diagnosismentioning
confidence: 99%
“…The easiest alternative is to switch the protease inhibitor for another antiviral drug; if necessary, paclitaxel and a protease inhibitor may be associated, with close monitoring [63]. Bleomycin and vinblastine show poor response when used as monochemotherapy and are usually combined with pegylated liposomal doxorubicin [59]. Furthermore, chemotherapy induces additional immunodeficiency, which necessitates prophylaxis against pneumocystosis and toxoplasmosis.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…However, according to a small randomized study that was not sufficiently powered, it appears to be slightly less effective than pegylated liposomal doxorubicin [21]. Another option is paclitaxel, which has shown similar response rates in a small randomized trial on patients with advanced KS [22]. However, paclitaxel is more myelotoxic and almost always leads to complete alopecia, often during the very first cycle.…”
Section: Chemotherapy and Immunotherapymentioning
confidence: 99%